Galois Theory for Finite Algebras of Operations and Multioperations of Rank 2 - N.A. Peryazev (Известия Иркутского государственного университета: Серия "Математика", 2019)
The construction of Galois theory for the algebras of operations and relations is a popular topic for investigation. It finds numerous applications in both algebra and discrete mathematics – especially for the perfect Galois connection, since if such a connection is established for the sets of all subalgebras of some algebra then the algebraic closure in this algebra coincides with the Galois closure, and this is an efficient tool for solving many algebraic problems. The perfect Galois connection is well known for clones and co-clones, as well as for some algebras of operations, for example, for clones and superclones.